2005
DOI: 10.1523/jneurosci.4740-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Control of Synaptic Connection by Glutamate Receptor δ2 in the Adult Cerebellum

Abstract: Precise topological matching of presynaptic and postsynaptic specializations is essential for efficient synaptic transmission. Furthermore, synaptic connections are subjected to rearrangements throughout life. Here we examined the role of glutamate receptor (GluR) ␦2 in the adult brain by inducible and cerebellar Purkinje cell (PC)-specific gene targeting under the pure C57BL/6 genetic background. Concomitant with the decrease of postsynaptic GluR␦2 proteins, presynaptic active zones shrank progressively and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
137
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(143 citation statements)
references
References 54 publications
6
137
0
Order By: Relevance
“…There is clear evidence that postsynaptic GluR␦2 plays an essential role in vivo in the formation and maintenance of the PF-PC synapse in the cerebellum (Kashiwabuchi et al, 1995;Kurihara et al, 1997;Takeuchi et al, 2005). Recently, we revealed that GluR␦2 mediates PF-PC synapse formation in vivo by interacting with presynaptic NRXNs through Cbln1 (Uemura et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…There is clear evidence that postsynaptic GluR␦2 plays an essential role in vivo in the formation and maintenance of the PF-PC synapse in the cerebellum (Kashiwabuchi et al, 1995;Kurihara et al, 1997;Takeuchi et al, 2005). Recently, we revealed that GluR␦2 mediates PF-PC synapse formation in vivo by interacting with presynaptic NRXNs through Cbln1 (Uemura et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…GluR␦2 is selectively expressed in cerebellar PCs (Araki et al, 1993;Lomeli et al, 1993) and is exclusively localized at PF-PC synapses (Takayama et al, 1996;Landsend et al, 1997). In conventional and conditional GluR␦2 knock-out mice, a significant number of PC spines lack synaptic contacts with PF terminals, and some of residual PF-PC synapses show mismatching between presynaptic and postsynaptic specializations (Kashiwabuchi et al, 1995;Kurihara et al, 1997;Takeuchi et al, 2005). These studies indicate that the formation and maintenance of PF-PC synapses are critically dependent on GluR␦2 in vivo.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…By the way, GluR␦2 also plays a role in stabilization of parallel fiber-PN synapse structure possibly through interaction with a molecule in the presynaptic active zone (Kurihara et al, 1997;Takeuchi et al, 2005;Hirano 2006). GluR␦2 is efficiently transported to plasma membrane and relatively evenly distributed in the postsynaptic density of parallel fiber-PN synapse.…”
Section: Discussionmentioning
confidence: 99%
“…plays an important role in the formation and maintenance of the PF-PC synapse (Guastavino et al, 1990;Kashiwabuchi et al, 1995;Kurihara et al, 1997;Lalouette et al, 2001;Takeuchi et al, 2005) through its selective expression at this synapse (Araki et al, 1993;Lomeli et al, 1993;Takayama et al, 1995;Landsend et al, 1997) and specific interaction of its N-terminal domain with presynaptic molecule neurexin through Cbln1 released from granule cells (Kashiwabuchi et al, 1995;Kurihara et al, 1997;Lalouette et al, 2001;Yuzaki, 2009;Matsuda et al, 2010;Uemura et al, 2010). Primary defects in GluRδ2-KO mice occur in the connectivity of PF-PC synapses, as manifested by the emergence of free spines and mismatching of pre-and postsynaptic specialization (Guastavino et al, 1990;Kurihara et al, 1997;Lalouette et al, 2001).…”
Section: Application To Glurδ2-ko Micementioning
confidence: 99%